The effectiveness of non-pyrethroid insecticide-treated durable wall lining to control malaria in rural Tanzania: study protocol for a two-armed cluster randomized trial. (December 2016) - Mtove, George; Mugasa, Joseph; Messenger, Louisa; Malima, Robert; Mangesho, Peter; Magogo, Franklin; Plucinski, Mateusz; Hashimu, Ramadhan; Matowo, Johnson; Shepard, Donald; Batengana, Bernard; Cook, Jackie; et al.
Abstract Background Despite considerable reductions in malaria achieved by scaling-up long-lasting insecticidal nets (LLINs) and indoor residual spraying (IRS), maintaining sustained community protection remains operationally challenging. Increasing insecticide resistance also threatens to jeopardize the future of both strategies. Non-pyrethroid insecticidetreated wall lining (ITWL) may represent an alternate or complementary control method and a potential tool to manage insecticide resistance. To date no study has demonstrated whether ITWL can reduce malaria transmission nor provide additional protection beyond the current best practice of universal coverage (UC) of LLINs and prompt case management. Methods/design A two-arm cluster randomized controlled trial will be conducted in rural Tanzania to assess whether non-pyrethroid ITWL and UC of LLINs provide added protection against malaria infection in children, compared to UC of LLINs alone. Stratified randomization based on malaria prevalence will be used to select 22 village clusters per arm. All 44 clusters will receive LLINs and half will also have ITWL installed on interior house walls. Study children, aged 6 months to 11 years old, will be enrolled from each cluster and followed monthly to estimate cumulative incidence of malaria parasitaemia (primary endpoint), time to first malaria episode and prevalence of anaemia before and after intervention. Entomological inoculation rate will be estimated using indoor CDC light traps and outdoor tent traps followed by detection ofAnopheles gambiae species, sporozoite infection, insecticide resistance and blood meal source. ITWL bioefficacy and durability will be monitored using WHO cone bioassays and household surveys, respectively. Social and cultural factors influencing community and household ITWL acceptability will be explored through focus-group discussions and in-depth interviews. Cost-effectiveness, compared between study arms, will be estimated per malaria case averted. Discussion This protocol describes the large-scale evaluation of a novel vector control product, designed to overcome some of the known limitations of existing methods. If ITWL is proven to be effective and durable under field conditions, it may warrant consideration for programmatic implementation, particularly in areas with long transmission seasons and where pyrethroid-resistant vectors predominate. Trial findings will provide crucial information for policy makers in Tanzania and other malaria-endemic countries to guide resource allocations for future control efforts. Trial registration NCT02533336 registered on 13 July 2014.